Analysis of Cybercrime as a Negative Impact of Technological and Internet Development in Indonesia Based on Law Number 19 of 2016 from a Criminal Law Perspective (Judge's Decision Study No. 569/Pid.sus/2022/PN.Btm) - Ternando, Albi; Dwianggara, Dany; Rahman, Rahman; Indara, Rona; Tatiana, Orid (Jurnal Smart Hukum (JSH), 2025)
The rapid development of information and communication technology has brought significant benefits to society, but on the other hand, it has also given rise to various threats, including cybercrime. In Indonesia, the increase in cybercrime cases, such as skimming, has caused major economic losses and threatened the stability of digital security. This study focuses on the factors causing the increase in cybercrime and efforts to prevent it. The research method used is a normative legal approach through a literature review that studies related laws and regulations, including Law No. 11 of 2008 concerning Information and Electronic Transactions which was updated in 2016. The results of the study indicate that the main causes of cybercrime include weak network security, low digital literacy of the community, and limitations in law enforcement. This study recommends strengthening regulations, increasing human resource capacity, and implementing technology-based prevention policies as solutions to combat cybercrime. This study is expected to be a reference for policy makers and legal practitioners in dealing with cybercrime problems in Indonesia effectively.